Oncological safety of hysteroscopy in the diagnosis of stage I endometrial cancer: protocol for a systematic review and meta-analysis - Yu Xu; Qian Wen Zhang; Yi Du; Zhao Juan Qin; Yue Dong He; Ai Zheng (BMJ Open)
Background The oncological safety of diagnostic hysteroscopy in patients with stage Ⅰ endometrial cancer remains uncertain and conflicting. The aim of the proposed systematic review and meta-analysis is to summarise the available evidence examining the association between diagnostic hysteroscopy and the prognosis of stage Ⅰ endometrial cancer and to statistically synthesise the results of relevant studies.Methods and analysis Systematic searches of PubMed/MEDLINE, Embase, Cochrane Library and Web of Science will be undertaken using prespecified search strategies. Two authors will independently conduct eligible studies selection process, perform data extraction and appraise the quality of included studies. Original case–control studies, cohort studies and randomised controlled trails published in English will be considered for inclusion. The outcomes of interest will be 5-year recurrence-free survival, disease-specific survival and overall survival. Meta-analyses will be performed to calculate pooled estimates.Ethics and dissemination Our study will be based on published data, and thus there is no requirement for ethics approval. The results will be shared through publication in a peer-reviewed journal and presentations at academic conferences.PROSPERO registration number CRD42020193696.